Macrophage Migration Inhibitory Factor -173 G/C Polymorphism: A Global Meta-Analysis across the Disease Spectrum - Illescas, Oscar; Gomez-Verjan, Juan C.; García-Velázquez, Lizbeth; Govezensky, Tzipe; Rodriguez-Sosa, Miriam (Frontiers in Genetics, 2018)
Human macrophage migration inhibitory factor (MIF) is a cytokine that plays a role in several metabolic and inflammatory processes. Single nucleotide polymorphism (SNP) -173 G/C (rs755622) on MIF gene has been associated with numerous diseases, such as arthritis and cancer. However, most of the reports concerning the association of MIF with these and other pathologies are inconsistent and remain quite controversial. Therefore, we performed a meta-analysis from 96 case-control studies on -173 G/C MIF SNP and stratified the data according to the subjects geographic localization or the disease pathophysiology, in order to determine a more meaningful significance to this SNP. The polymorphism was strongly associated with an increased risk in autoimmune-inflammatory, infectious and age-related diseases on the dominant (OR: 0.74 [0.58-0.93], P-val<0.01; OR: 0.81 [0.74-0.89], P-val<0.0001; and OR: 0.81 [0.76-0.87], P-val<0.0001, respectively) and the recessive models (OR: 0.74 [0.57-.095], P-val<0.01; OR: 0.66 [0.48-0.92], P-val<0.0154; and OR: 0.70 [0.60-0.82], P-val<0.0001, respectively). Also, significant association was found in the geographic localization setting for Asia, Europe and Latin America subdivisions in the dominant (OR: 0.76 [0.69-0.84], Pval: <0.0001; OR: 0.77 [0.72-0.83], Pval: <0.0001; OR: 0.61 [0.44-0.83], Pval: 0.0017, respectively) and overdominant models (OR: 0.85 [0.77-0.94], Pval: <0.0001; OR: 0.80 [0.75-0.86], Pval: <0.0001; OR: 0.73 [0.63-0.85], Pval: 0.0017, respectively). Afterwards, we implemented a network meta-analysis to compare the association of the polymorphism for two different subdivisions. We found a stronger association for autoimmune than for age-related or autoimmune-inflammatory diseases, and stronger association for infectious than for autoimmune-inflammatory diseases. We report for the first time a meta-analysis of rs755622 polymorphism with a variety of stratified diseases and populations. The study reveals a strong association of the polymorphism with autoimmune and infectious diseases. These results may help direct future research on MIF -173 G/C in diseases in which the relation is clearer and thus assist the search for more plausible applications.